Antioxidant capacity, phenolic and vitamin C contents of quinoa (Chenopodium quinoa Willd.) as affected by sprouting and storage conditions - Laus, Maura N.; Cataldi, Mariagrazia P.; Robbe, Carlo; D'Ambrosio, Tiziana; Amodio, Maria L.; Colelli, Giancarlo; De Santis, Giuditta; Flagella, Zina; Pastore, Donato (Italian Journal of Agronomy, 2017)
Antioxidant capacity (AC) of quinoa (Chenopodium quinoa Willd. cv. Real) seeds and sprouts obtained after 4 days of seed germination at 20Â°C and 70% humidity was evaluated using trolox equivalent antioxidant capacity (TEAC) and oxygen radical absorbance capacity (ORAC) assays, able to highlight reducing activity and peroxyl radical scavenging capacity, respectively; phenolic content (PC) was also measured. Both TEAC and ORAC assays revealed a significantly higher (about 2- and 2.8-fold, respectively) AC of 4-day-old sprouts compared to seeds; consistently, also PC values of sprouts resulted about 2.6 times higher than seeds. In order to investigate the influence of storage on AC and PC, as well as on vitamin C content (VCC), 4-day-old sprouts were subjected for 7 days at 5Â°C to three different conditions of controlled atmosphere storage (CAS) compared with air. Interestingly, whatever the CAS conditions, storage of quinoa sprouts up to 7 days induced an increase of AC evaluated in terms of reducing activity by TEAC assay. Consistently, an increase of PC and VCC was measured during storage, positively correlated to TEAC values. Moreover, a decrease of peroxyl radical scavenging activity, measured by ORAC, was observed after 7 days of storage, in accordance with a shift of AC towards the reducing activity component. Overall, these findings indicate that sprouting approach using quinoa may provide highly antioxidant-enriched seedlings that may improve nutritional quality of diet or of functional foods. Interestingly, antioxidant properties of quinoa sprouts may be deeply influenced by storage, able to increase reducing activity by increasing phenols and vitamin C.